1991
DOI: 10.1128/jcm.29.4.718-722.1991
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Baxter-MicroScan 4-hour enzyme-based yeast identification system

Abstract: A new 4-h Yeast Identification Panel (YIP; Baxter-MicroScan, W. Sacramento, Calif.) was compared with the API 20C Yeast Identification System (Analytab Products, Inc., Plainview, N.Y.) in the identification of recent clinical yeast isolates. The YIP had a 94% correlation (288 of 306) in identifying 22 species within the genera Candida, Hansenula, Pichia, Rhodotorula, Saccharomyces, and Torulopsis. Correlation dropped to 65% for those species within the genera of slower growing yeasts, i.e., Blastoschizomyces s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 18 publications
0
20
0
2
Order By: Relevance
“…Similarly, the MicroScan Rapid Yeast identification panel (Baxter-MicroScan, W. Sacramento, CA, USA) tests for the presence of 27 preformed candidal enzymes. As growth is not a pre-requisite, the MicroScan system provides rapid identification after 4 h. Evaluations of the MicroScan for yeast identification have reported an accuracy of between 92.1% and 99.5% compared with morphological tests and the API-20 C (Land et al, 1991; St-Germain and Beauchesne 1991).…”
Section: Instrumental-based Identification Systemsmentioning
confidence: 99%
“…Similarly, the MicroScan Rapid Yeast identification panel (Baxter-MicroScan, W. Sacramento, CA, USA) tests for the presence of 27 preformed candidal enzymes. As growth is not a pre-requisite, the MicroScan system provides rapid identification after 4 h. Evaluations of the MicroScan for yeast identification have reported an accuracy of between 92.1% and 99.5% compared with morphological tests and the API-20 C (Land et al, 1991; St-Germain and Beauchesne 1991).…”
Section: Instrumental-based Identification Systemsmentioning
confidence: 99%
“…The reliability of the enzyme-based MicroScan kit for identifying common foodborne yeasts is also in question in light of the observation that some strains did not produce identical reactions in repeated tests. Inconsistent results were also noted by Land et al (1991b) when isolates were retested. Nevertheless, it cannot be concluded that the MicroScan system is unreliable, because variations in results are possible even to this extent, and correct identification can be achieved if these variations are properly considered in the biocode index.…”
Section: Discussionmentioning
confidence: 80%
“…The MicroScan yeast panel introduced later and improved recently appears to be more reliable. The panel gave 85% correlation with the API 20C kit for all yeasts tested in one study (Land et al 1991b) and increased up to 92% for common clinical isolates. When the MicroScan system was supplemented with a few morphological and conventional tests, its accuracy reached 96.6% (St-Germain and Beauchesne 1991).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…was similar to that of the first laboratory. Land et al (67) reported that only 27% of serogroup D isolates of Cryptococcus neoformans, which are common to Europe and other temperate regions, were correctly identified by the MicroScan YIP. On the other hand, 83% of serogroups B and C, serogroups geographically found nearest to the manufacturer, were correctly identified.…”
Section: Discussionmentioning
confidence: 99%